ANALISIS HUBUNGAN PERTUMBUHAN EKONOMI TERHADAP INVESTASI DAN PENYERAPAN TENAGA KERJA DI KABUPATEN/KOTA PROVINSI SULAWESI TENGAH - Tobigo, Haeruddin (Katalogis, 2019)
This research is conducted in the Governance of Central Sulawesi Province in accordance with the economic growth, investment and employment by using qualitative-descriptive analysis in order to explain the datas which are related to. The economic growth is able to be only measured from the PDRB or PDB (product domestic bruto) of Central Sulawesi while the investment will consider the use of capital for many sectors and the employment is divided into autonomous employment and not-working labor. The result of this research shows that the economic growth which is based on the bruto regional domestic income has a firm relation to the investment, the better economic growth then the better investment atmosphere in the local area. Moreover, the economic growth has an impact to the absorption of employment in Central Sulawesi.